Philippines-Malaysia diplomatic relations: policies and guidelines on the deployment management for Filipino deportees - Albidri Baharil Albi; Ali Maksum; Sugengriyonto Sugeng; Fathraena Amil (JURNAL ILMU SOSIAL, 2025)
Philippines-Malaysia diplomatic relations are multifaceted, balancing cooperation and contention across security, economic collaboration, and migration management. This research fills a critical gap by linking high-level Philippines—Malaysia diplomacy with the practical realities of deportation and reintegration, bridging migration policy and human rights concerns. This study analyzes key policies on Filipino deportee management and their impact on Philippines-Malaysia diplomatic relations using Neoliberal Institutionalism and the Human Security Framework, and it aims to determine how both nations handle diplomatic and operational aspects of deportation management. This research employs a descriptive mixed-methods design, combining qualitative survey essays and quantitative data from primary sources to evaluate Malaysia-Philippines diplomatic relations and assess policies and guidelines for managing the deployment of Filipino deportees. The study reveals that while the Philippines and Malaysia benefit from diplomatic cooperation through ASEAN, there is no direct bilateral agreement specifically addressing deportation management. Malaysia’s deportation system is technologically advanced, but deportees face significant challenges, such as poor detention conditions and limited reintegration support from the Philippines. The findings, analyzed through Neoliberal Institutionalism and the Human Security Framework, highlight a disconnect between state cooperation and the human needs of deportees, with gaps in legal, social, and psychological support during the deportation and reintegration process. Strengthening bilateral agreements on deportation, ensuring comprehensive consular support, and improving reintegration programs are essential to protect Filipino deportees. Integrating human security into diplomatic and operational practices will help both the Philippines and Malaysia establish a more humane, coordinated, and rights-based approach to managing deportation and reintegration challenges effectively.